2013
DOI: 10.1080/01635581.2013.776091
|View full text |Cite
|
Sign up to set email alerts
|

β-Ionone Induces Cell Cycle Arrest and Apoptosis in Human Prostate Tumor Cells

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase is the rate-limiting activity in the mevalonate pathway that provides essential intermediates for posttranslational modification of growth-associated proteins. Assorted dietary isoprenoids found in plant foods suppress HMG CoA reductase and have cancer chemopreventive activity. β-Ionone, a cyclic sesquiterpene and an end-ring analog of β-carotene, induced concentration-dependent inhibition of the proliferation of human DU145 (IC50 = 210 μmol/L) and LNCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 47 publications
1
10
0
3
Order By: Relevance
“…We found that the beta-ionone significantly in- showed β-ionone has an inhibitory effect on human gastric adenocarcinoma cells growth [21]. It would be compatible with the research by Zhu et al who have studied the effect of β-ionone on in human osteosarcoma (U2os) cells and has showed that this plant-derived compound is able to inhibit cell proliferation [22], also compatible with the research by Jones et al that examined the effect of β-ionone in human prostate tumor cells, and showed that β-ionone inhibited cell proliferation and activates apoptosis via the mitochondrial pathway [23]. In this case, similar observations have been reported in the previous studies with other natural plant products such as lycopene [24,25], silymarin [26], curcumin [27], epigallocatechin-3-gallate [28], celastrol [29], tea polyphenol [30], berberine [31], gossypol [32], wogonin [33], Korean red ginseng extract [34] and Curcuma longa extract [35] in various cancer cell lines.…”
Section: Discussionsupporting
confidence: 78%
“…We found that the beta-ionone significantly in- showed β-ionone has an inhibitory effect on human gastric adenocarcinoma cells growth [21]. It would be compatible with the research by Zhu et al who have studied the effect of β-ionone on in human osteosarcoma (U2os) cells and has showed that this plant-derived compound is able to inhibit cell proliferation [22], also compatible with the research by Jones et al that examined the effect of β-ionone in human prostate tumor cells, and showed that β-ionone inhibited cell proliferation and activates apoptosis via the mitochondrial pathway [23]. In this case, similar observations have been reported in the previous studies with other natural plant products such as lycopene [24,25], silymarin [26], curcumin [27], epigallocatechin-3-gallate [28], celastrol [29], tea polyphenol [30], berberine [31], gossypol [32], wogonin [33], Korean red ginseng extract [34] and Curcuma longa extract [35] in various cancer cell lines.…”
Section: Discussionsupporting
confidence: 78%
“…Farnesol, a typical isoprenol, has been reported to exhibit protective effects against many human cancers, such as lung, prostate, and colon cancer ( Au-Yeung et al, 2008 ; Jones et al, 2013 ; Gliszczyńska et al, 2016 ). Farnesol also has a critical role in the amelioration of inflammatory reactions by regulating major inflammation-related factors including proinflammatory cytokines, cyclooxygenase-2, and nitric oxide synthase ( Inoue et al, 2000 ; Ku and Lin, 2015 ; Santhanasabapathy et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, embora a BI apresente a capacidade de modular tanto a proliferação celular quanto a apoptose (Liu et al, 2004, Janakiram et al, 2010, Jones et al, 2013) "in vitro", em nosso estudo "in vivo" não houve diferença no índice apoptótico do grupo AS+BI em relação ao grupo AS nas pLPN e rLPN, estes resltados corroboram com estudo prévio do grupo no qual a BI não modulou a apoptose em pLPN (Cardozo et al, 2010). Entretanto, a proliferação celular em pLPN foi reduzida no grupo AS+BI, demonstrando seu potencial quimiopreventivo nestas lesões que comumente evoluem para o HCC (Schulte-Hermann, 1990;De Miglio et al, 2003).…”
Section: Discussionunclassified
“…Entretanto, a proliferação celular em pLPN foi reduzida no grupo AS+BI, demonstrando seu potencial quimiopreventivo nestas lesões que comumente evoluem para o HCC (Schulte-Hermann, 1990;De Miglio et al, 2003). Relata-se que a BI suprime a proliferação por induzir a parada do ciclo celular na fase G1 de células neoplásicas de melanoma murino B16, leucemia promielocítica aguda humana HL-60, de adenocarcinoma do cólon humano Caco-2 e HCT116 (Jones et al, 2013). O ciclo celular é dirigido pela família de proteínas conhecidas como ciclinas dependentes de quinase (CDKs), a associação das CDKs com as ciclinas (A, B, D e E) forma complexos denominados Ciclina/CDK, que são ativados e promovem fosforilação de sítios específicos em CDKs, resultando no funcionamento normal do ciclo celular (Schwartz, 2002;Lopez-Mejia & Fajas, 2015).…”
Section: Discussionunclassified